PENGARUH MODEL PEMBELAJARAN TRANSDISCIPLINARY TERHADAP KARAKTER SISWA PADA SEKOLAH DASAR INTERNASIONAL BERBASIS INTERNATIONAL BACCALAUREATE - Sunaengsih, Cucun (Universitas Pendidikan Indonesia, 2015)
Development of learning innovations embodied in the learning model into the main needs within the education system in order to shape the character of qualified students. There are many models of learning that can shape the character of students. The learning models which are considered to establish the character among the students are developed based on an international school-based International Baccalaureate (IB) which Trandisciplinary or trans disciplinary learning model. Trans disciplinary model is considered to be most able to form the character of the students because it integrates various disciplines of science to create an understanding of the whole. The method used in this research is a survey research with quantitative research approaches. As for the population in this study are all teachers who exist in the International Primary School-Based IB in Bandung. The results showed that the learning model Trandisciplinary positive and significant impact on the character among the students. Second correlation value is at a high position.Keywords: trans disciplinary learning model, character students, and the international baccalaureate.